Psychometric evaluation of the Malay adolescent coping scale (acs): A study of Malaysian adolescents - Ferlis Bullare @ Bahari (IMPACT Journals, 2015)
The aim of the study is to assess the psychometric of the Adolescent Coping Scale (ACS) that involves internal consistency reliability, test-retest reliability, and item-scale correlation for Short Form items. Internal consistency reliability of ACS was measured using alpha Cronbach method while test-retest reliability was measured using Pearson correlation coefficient method. To assess the degree to which each of the items in the Short-Form adequately measured its respective coping strategy, the correlation of the item with the scale of which it was a part was computed. The research subjects consist of 3158 adolescents aged between 13 to 19 and was selected using purposive sampling. The instrument of Adolescent Coping Scale (ACS) by Frydenberg and Lewis {1993 was used. Research finding for ACS Specific and ACS General Long Form instrument are both has a high internal consistency value which were 0.928 and 0.922. While internal consistency by test-retest method for ACS Specific and ACS General Long Form both noted an alpha value of 0.933 and 0.928. Lastly, validity analyses by item-scale correlation of 18 ACS Short Form items gain correlation value about 0.605 and 0.869 for General Form and 0.873 for Specific Form. In conclusion, the finding shows that ACS instrument in Bahasa Malaysia version is suitable to be use as an objective tool in measurement and assessment in the coping strategies for adolescents who facing problems and can help them toward a better quality of life. This is not just coping, but positive coping should reduce the burden of challenges of both sho1i-term immediate stress and should also contribute to longer-term stress relief. In line with a positive psychology orientation, some ways of dealing with stress may actually help to build more effective coping resources for the future.